2018
DOI: 10.1002/bjs.10880
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effect of bariatric surgery on physical function

Abstract: Bariatric surgery improves physical function significantly within 6 months of the procedure and this effect persists over time to 36 months after surgery, whether measured objectively or by self-reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 71 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…After BS, many aspects are modified and imply a reduction in the risk of obesity-associated disorders as well as of all-cause mortality (911). Some of the beneficial effects of BS are improved physical function (12), sustained weight loss, reduction of comorbidities such as osteoarthritis and respiratory dysfunction (13), a more favorable metabolic profile, which implies an improvement in quality of life, and the resolution of cardiovascular risk factors (1419) with lower triglyceride levels and higher HDL-C levels in most patients 1 year after surgery (20, 21).…”
Section: Bariatric Surgery (Bs): a Treatment For Obesitymentioning
confidence: 99%
“…After BS, many aspects are modified and imply a reduction in the risk of obesity-associated disorders as well as of all-cause mortality (911). Some of the beneficial effects of BS are improved physical function (12), sustained weight loss, reduction of comorbidities such as osteoarthritis and respiratory dysfunction (13), a more favorable metabolic profile, which implies an improvement in quality of life, and the resolution of cardiovascular risk factors (1419) with lower triglyceride levels and higher HDL-C levels in most patients 1 year after surgery (20, 21).…”
Section: Bariatric Surgery (Bs): a Treatment For Obesitymentioning
confidence: 99%
“…A number of structured or systematic reviews have shown that the HRQoL of patients suffering from obesity improved after surgery. [28][29][30][31][32][33] However, these studies are mainly comprised of disease-specific (e.g., Moorehead-Ardelt II questionnaire [MA-II]) or non-preference-based (e.g., Short Form [SF]-36) data that are unsuitable for cost-utility comparisons because they do not generate a utility value. An emerging literature has shown that HSUs have been used as a metric for quantifying HRQoL improvements regarding bariatric surgery, nevertheless, meta-analyses of bariatric surgery-related HSUs have not been conducted to date.…”
Section: Bariatric Surgery-related Hrqol and Research Gapsmentioning
confidence: 99%
“…The physical fitness actually is prognostically more important than adiposity in obese individuals [31]. After bariatric surgery the functional capacity (as assessed by the 6-min walking test (6MWT)) or self-reported physical fitness increases significantly [32,33]. However, this does not indicate that exercise capacity (as preferentially assessed by ergospirometry to measure peak oxygen uptake (VO2peak)) is actually improved.…”
Section: Importance Of Physical Activity and Exercise Intervention After Bariatric Surgerymentioning
confidence: 99%